Pelatihan Bidan dalam Penggunaan Peanutball bagi Ibu hamil yang Mengalami Ketuban Pecah Dini di Wilayah Kerja Puskesmas Ujanmas Kabupaten Muara Enim Sumatera Selatan - Fatimah, Siti; Retnosari, Ekadewi; Dahliana, Dahliana; Khairunisya, Khairunisya; MP, Nia Clarasari (Universitas Baiturrahim, 2024)
Premature rupture of membranes (KPD) occurs in 5% of pregnancies worldwide. PROM causes limited movement in the labor position and inhibits fetal descent. Peanut balls are designed from elastic material in the shape of a peanut and are easy to use to open the pelvis, allowing for better fetal descent. However, there are still few midwives who understand its use in situations where pregnant women have limited movement. This service provides training to midwives in providing birth care to mothers with KPD. The method for implementing this activity uses peanut ball training. Participants are given knowledge and skills assessment instruments that are measured before and after community service activities. The service implementation was carried out in the Ujanmas Community Health Center Work Area, Muara Enim Regency, in 2023. The service team trained 18 midwives who were willing to take part in the training. The results showed that the midwives' knowledge about the use of peanut balls in KPD patients was initially mostly lacking (76%), but in the beginning At the end of the service most of them were good (90%). At the start of the service, none of the midwives' skills were able to use peanut balls on women giving birth, but at the end of the service, 100% of the midwives became skilled at using peanut balls. This peanut ball training has been proven to improve midwives' skills in providing care to mothers with premature rupture of membranes.